AZ-900 Azure fundamentals crash course. (Packt Publishing, 2023)
In today's technology-driven world, cloud computing is a game-changer, and Microsoft Azure stands at the forefront. Azure is the backbone of countless businesses, offering scalable, flexible, and secure cloud solutions. To navigate this landscape, understanding the fundamentals is paramount, and the AZ-900 certification is your ticket to Azure mastery. This course is your comprehensive guide to mastering Azure basics and conquering the AZ-900 exam. Starting with an introduction to cloud computing, you will grasp the benefits of cloud services and dive deep into Azure's core architectural components. You will explore compute and networking services, storage solutions, and identity and security in the Azure environment. Gain prowess in cost management, governance, compliance, and monitoring tools. The course also culminates with a detailed exploration of Azure Advisor, Azure Service Health, and Azure Monitor, giving you an arsenal of tools to optimize Azure resources. By the end of this course, you will be proficient in Azure cloud computing principles, well-prepared to ace the AZ-900 exam, and equipped to excel in the world of Microsoft Azure. What You Will Learn Understand core Azure principles and cloud computing fundamentals Create scalable Azure infrastructure with architectural components Explore Azure's compute, networking, and storage services in-depth Implement identity, access, and security features for Azure resources Build cost-efficient solutions while ensuring compliance and governance Master Azure monitoring tools for robust resource management Audience This course caters to both newcomers and aspiring cloud enthusiasts. If you're stepping into the world of cloud computing, seeking a strong foundation in Microsoft Azure fundamentals, or aiming to enhance your existing cloud knowledge, this course is designed for you. No prior experience with Azure or cloud computing is necessary. All that's required is your curiosity and willingness to learn. About The Author Praveenkumar Bouna: Praveenkumar Bouna is a software engineer with over 15 years of C# .NET development experience. He holds a Bachelor of Engineering in computer science and engineering. He has worked for about ten years in Honeywell, wherein he transitioned from software engineer to senior software engineer, tech lead, and so on in C#. He has also worked in security and surveillance as well as access control systems in top MNCs in the software industry. He is also a Certified ScrumMaster (CSM) and Scrum Master for a security R&D team. He is known for his simpler teaching approach toward explaining various complex topics his colleagues come across in everyday programming life.